2017
DOI: 10.4236/ajps.2017.83022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetic Variation and Relationships among a Mini Core Germplasm of Sesame (<i>Sesamum indicum</i> L.) Using Biochemical and RAPD Markers

Abstract: Knowledge of genetic diversity is essential for any future varietal improvement program. Thus, the objective of this study is to contribute to a better knowledge of the genetic diversity within 15 sesame accessions, using biochemical markers and RAPD. The accessions are of various sources and seeds of different colors; color being an important feature in the sesame market. SDS-PAGE on protein extracts of sesame seeds revealed 31 protein markers, only 4 of which were polymorphic, indicating that this technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
3
3
1
Order By: Relevance
“…Our findings exposed a limited level of diversity between the studied sesame genotypes. These findings agreed with Quenum et al ( Quenum and Yan, 2017 ), who exhibited a small level of intraspecific variability for seed protein between Sesame. Contrary, Nisar et al ( Nisar et al, 2007 ) showed a high level of intraspecific variability for seed protein between local and exotic chickpea germplasm.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings exposed a limited level of diversity between the studied sesame genotypes. These findings agreed with Quenum et al ( Quenum and Yan, 2017 ), who exhibited a small level of intraspecific variability for seed protein between Sesame. Contrary, Nisar et al ( Nisar et al, 2007 ) showed a high level of intraspecific variability for seed protein between local and exotic chickpea germplasm.…”
Section: Discussionsupporting
confidence: 93%
“…In our present study, the clustering pattern showed that 15 accessions are grouped into 3 to 5 clusters based on the scores of first six principal components (PCs) derived from six seed traits, revealing geographical diversity which is not strongly related to genetic diversity. This absence of relationship between genetic diversity and geographical distribution is in accordance with the findings of our previous works in sesame using agro-morphological and molecular markers (Quenum et al, 2004;Quenum and Yan, 2017). Similar results were reported by Kaushik et al, (2007b), Rao et al, (2008), Gohil and Pandya (2008) in Jatropha curcas; and Kaushik et al (2007a) in Pongamia pinnata.…”
Section: Morphological Diversity Of Seeds and Their Relationshipssupporting
confidence: 92%
“…The genetic similarity coefficient observed in this study, 0.58 -0.92 in the case of RAPD; 0.78 -0.95 in the case of ISSR and 0.72-0.94 in case of pooled data of RAPD and ISSR. These results are confirmed by Dar et al (2017) reported that the similarity coefficient of RAPD ranged from 0.51 to 0.88, and ranged from 0.34 to 0.89 between 15 sesame accessions by Quenum and Yan (2017). Whilst, our results were high compared with previous studies by Parsaeian et al (2011) in which the coefficient of similarities ranged from 0.09 to 0.55.…”
Section: Molecular Analysissupporting
confidence: 88%